Efektivitas E-Rapor di SMK Negeri Kota Padang - Rahma Sari, Fadhilah; Ahmad Sabandi (Global Action and Education for Society, 2024)
This research was motivated by problems regarding the effectiveness of e-reports at Padang City Vocational Schools according to teachers' perceptions. The aim of this research is to explore information about the effectiveness of e-reports according to homeroom teachers' perceptions in terms of achieving goals, adaptation and job satisfaction. The research was conducted using a quantitative descriptive method with a population of 248 homeroom teachers at SMKN and a sample of 73 people was selected using the Slovin formula and the Stratified Random Sampling technique. The results of the research show that the effectiveness of e-reports in Padang City Vocational Schools according to teachers' perceptions obtained an average score of 4.17 in the high/capable category. From these results it can be concluded that the homeroom teacher's perception of the effectiveness of e-reports at SMKN Padang City is said to be high/capable